Avaliação das características físico-químicas e microbiológicas dos componentes fibrosos obtidos da moagem úmida de grãos de milho - Rocha-Olivieri, Camila Mattos [UNESP]; Conti-Silva, Ana Carolina [UNESP]; Lopes-Filho, Jose Francisco [UNESP] (My University, 2012)
Fibers are non-digestible materials by human organism, and they are insoluble in specific conditions. The corn fiber has been used as an alternative to enrich the food products for human consumption, in order to add nutritious value to this co-product. This study aimed at determining the chemical and fractions components of corn fiber, extracted by semi-wet milling in laboratory (LabF), and by semi-humid milling in industrial process (IndF); and microbiological analyses were perform in the last fraction. The fiber composition differed significantly among these two products as to moisture, ash, lipids, proteins, insoluble dietary fiber, neutral detergent fiber (NDF), acid detergent fiber (ADF), cellulose and lignin contents. The sample IndF showed microbiological parameters in compliance with the specifications for consumption. The investigated corn fiber may effectively contribute to increase the fiber intake in the diet. As the industrially processed fiber (IndF) showed compliant microbiological parameters with the specifications for food, this component might be incorporated into the food products formulation.

As fibras são materiais não digeríveis pelo organismo humano e insolúveis em condições específicas. A fibra do milho tem sido utilizada como componente alternativo para enriquecer produtos alimentícios destinados ao consumo humano, com o intuito de agregar valor a esse coproduto. No presente estudo foram determinadas as características químicas e as frações componentes de fibras de milho, extraídas por moagem úmida, em laboratório (FLab), e moagem semiúmida, em processo industrial (FInd); neste último produto foi realizada análise microbiológica. A composição das fibras diferiu estatisticamente entre ambas as amostras (p < 0,05) quanto aos teores de umidade, cinzas, lipídeos, proteínas, fibra alimentar insolúvel, fibra em detergente neutro (FDN), fibra em detergente ácido (FDA), celulose e lignina. A amostra FInd demonstrou parâmetros microbiológicos em conformidade com as especificações adequadas para o consumo. As fibras de milho estudadas podem contribuir efetivamente para o aumento do aporte de fibras na dieta alimentar. Em vista da fibra obtida pelo FInd ter demonstrado parâmetros microbiológicos em conformidade com as especificações para alimentos, esse componente poderá ser incorporado na formulação de produtos alimentícios.
Physical-chemical and microbiological characteristics of fibrous components obtained from corn wet milling
Keywords: Milho; Moagem Umida; coproduto; fibra alimentar; milho; moagem úmida